2000
DOI: 10.1093/toxsci/58.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylesterase and A-Esterase Activities during Maturation and Aging: Relationship to the Toxicity of Chlorpyrifos and Parathion in Rats

Abstract: Chlorpyrifos (CPF) and parathion (PS), two common organophosphorus (OP) pesticides, exhibit higher acute toxicity in younger animals compared to adults. Maturational differences in detoxification via carboxylesterases (CEs) and A-esterases (AEs) have been suggested as contributors to the higher sensitivity of younger animals to OP toxicants. AEs (e.g., chlorpyrifos oxonase and paraoxonase) catalytically inactivate while CEs stoichiometrically eliminate OP anticholinesterases. While earlier studies have reporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 49 publications
5
72
2
Order By: Relevance
“…The maturing animals viz., neonates and juveniles are more susceptible to acute toxic effects of CPF than young adults, primarily because of lower levels of detoxifying enzymes. The detoxification of CPF include binding to carboxylesterases and hydrolysis by arylesterases [26] and these mechanisms appear to have got altered differentially in different age group of rats since physiologic systems differ in different age group leading to homeostatic alterations, as a result the ability to respond adequately to toxic stress or insult varies. Young animals are unique because of the immature nervous system which responds differentially to the exposure of CPF with its kinetic ability (absorption, distribution, metabolism & excretion).…”
Section: Discussionmentioning
confidence: 99%
“…The maturing animals viz., neonates and juveniles are more susceptible to acute toxic effects of CPF than young adults, primarily because of lower levels of detoxifying enzymes. The detoxification of CPF include binding to carboxylesterases and hydrolysis by arylesterases [26] and these mechanisms appear to have got altered differentially in different age group of rats since physiologic systems differ in different age group leading to homeostatic alterations, as a result the ability to respond adequately to toxic stress or insult varies. Young animals are unique because of the immature nervous system which responds differentially to the exposure of CPF with its kinetic ability (absorption, distribution, metabolism & excretion).…”
Section: Discussionmentioning
confidence: 99%
“…Converging evidence suggests that CES1 function in juvenile animals remain at a significantly lower level than that of adult animals (Kadner et al, 1992;Morgan et al, 1994;Moser et al, 1998;Karanth and Pope, 2000;Padilla et al, 2004;Anand et al, 2006). Animal studies demonstrated that juvenile rats did not hydrolyze oseltamivir efficiently, and they are more susceptible than adults to oseltamivir toxicity (http://www.fda.gov/cder/ foi/nda/2000/21-246_Tamiflu_Pharmr.pdf).…”
Section: Discussionmentioning
confidence: 99%
“…PNPA hydrolysis also decreased with age (Table 2), due presumably to downregulation of CES1 isozyme levels, although CESs are responsible for only 65% of the total hepatic microsomal hydrolysis of PNPA. Karanth and Pope (2000) reported that the hydrolase activity for PNPA was identical at 90 days (13 weeks) and 24 months (96 weeks) in the hepatic S9 fraction of Sprague-Dawley rats. In the present experiments, we used hepatic microsomal fractions from Wistar rats.…”
Section: Tablementioning
confidence: 98%
“…In the same rats, the hepatic intrinsic clearance of the pyrethroid deltamethrin, through oxidation by cytochrome P450 (P450), reaches maximum activity in 40-day-old rats. Karanth and Pope (2000) reported that hepatic activity against p-nitrophenyl acetate (PNPA) increases with age in rats and reaches maximum activity at 90 days, maintaining this level of activity up to 24 months, while maximal activity in plasma is reached at 90 days and has decreased by 24 months.…”
Section: Introductionmentioning
confidence: 99%